Refinements of Hardy-Type Inequalities - Jingfeng Tian; Yang-Xiu Zhou (Abstract and Applied Analysis)
Using Hu Ke's inequality, which is a sharped Hölder's inequality, we present some new refinements of Hardy-type inequalities proposed by Imoru.